Bridging Generations and Cultures: An Interdisciplinary Approach to Mother-Daughter Conflict and Storytelling in Amy Tan’s The Joy Luck Club (1989) - MAMMERI, Siham; BENTAHAR , Soumia (Faculty Of Letters And Foreign Languages Department Of Letters And English, 2024)
Chinese-Americans, one of the largest ethnic groups contributing to the shaping of the United States as a multicultural society, continue to maintain their cultural traditions despite their settlement in America, a country whose culture is completely different from their own. This group, particularly Chinese women, have endured significant hardships in the New World. One major challenge this thesis seeks to highlight is the conflict that arises between the immigrant Chinese mothers and their American-born daughters. Amy Tan, a prominent Chinese-American writer, uses fiction to address this conflict alongside other critical problems mainly encountered by Chinese-American female characters. Significantly, in her 1989 novel The Joy Luck Club, Tan not only problematizes mother-daughter relationship, but also attempts to offer a resolution to this predicament largely by recourse to storytelling and the mother figure. Therefore, an interdisciplinary approach is undertaken to understand how Amy Tan enables the female characters to transcend intergenerational conflict so as to eventually achieve reconciliation